ALIH KODE DAN CAMPUR KODE BAHASA INDONESIA DAN BAHASA BUGIS DALAM VIDEO BLOGGING (VLOG) - Yustina, Ade; Mardatillah, Rahmi; Apyunita, Devi (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
This study describe the forms of code switching and code mixing in vlogs and the factors causing them. This is a qualitative descriptive study. Data consists of utterances in the form of words, phrases, clauses, and sentences that contain elements of code switching and codemixing. Data sources were obtained from Baco Kuttu Management vlogs. Data collection was conducted using (1) participant observation and (2) note-taking techniques. Data were analyzed using the translational method to identify the forms of code-switching and codemixing, and the pragmatic matching method to identify the factors.The results showed that there was internal code-switching, namely code-switching from Indonesian to Bugis and vice versa. This code-switching was caused by the speaker's factors in explaining something and providing explanations as well as changes in the topic of conversation. The code-mixing found was in the form of code-mixing in words, phrases, clauses, and reduplication, caused by the speaker's background, attitude, and linguistic factors.